The Contribution of the Royal New Zealand Naval Hydrographic Surveyor - Gilbanks, R. J. (The International Hydrographic Review, 2015)
Some 200 years elapsed between the visit of Abel Tasman who first sketched New Zealand’s coastline and the commencement of the Great Survey of New Zealand by Captain John Lort Stokes, RN, in HMS Acheron. However, the several surveyors who did visit the country in those intervening years contributed in a major way to the growth of the nation and included the most famous, Lieutenant James Cook and the less well known, de Surville and d’ENTRECASTEAUX, Vancouver, Malaspina and Bauza. Between 1848 and 1949, visiting British naval officers conducted hydrographic surveys of increasing accuracy until the Hydrographic Department of the RNZN assumed the role in 1949. Subsequent to that date, a multitude of detailed surveys have been carried out by RNZN officers for national development projects and for general charting purposes. Charts have been compiled and published in New Zealand since 1950 and as there have been significant increases in the size of the area for which the RNZN has surveying and charting responsibility, it is anticipated that there will soon be up to 130 charts published by the Hydrographic Office. The cost of surveying and charting is very high, but the RNZN will retain the role because of its importance to the security of the nation and to the welfare of all mariners. The position of Hydrographer RNZN is a focal point for national and international dialogue concerning professional standards and user requirements and the Hydrographic Department is instrumental in providing assistance to neighbouring countries so that they may develop the skills to survey and chart their waters and thus better manage their resources. There are important challenges ahead. They include development of techniques, equipment and personnel to meet the requirements of surveying and charting amidst the rapidly advancing technology available. This paper outlines the contributions naval surveyors have made to date and their anticipated contributions in the future.